Student Spatial Skill Profile Based on Cognitive Style in Solving Mathematical Problems through Mathematical Questions Posing - Faridatul Masruroh, Faridatul Masruroh; Ama Noor Fikrati; Siti Dinarti (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2024)
The purpose of this study was to describe the spatial skills of mathematics education students at PGRI Jombang University based on field-dependent and field-independent cognitive styles. This study is a qualitative study. The subjects of the study were 2 mathematics education students at PGRI Jombang University, with details of 1 field-dependent student (SFD) and 1 field-independent student (SFI). The main instrument in this study was the researcher himself, while the supporting instruments were the student spatial skills test sheet and interview guidelines. The results showed that SFI was able to understand horizontal invariance but had not been able to apply it to more complex problems, was able to mention changes in the position of elements in a simple object but not in a complex object, was able to unite objects into more complex configurations, was able to combine two simple objects but not yet able to more complex objects, and was unable to visualize an environment as a whole from different positions. While SFD is able to understand horizontal invariance in more complex problems, mention changes in the position of elements in a complex object, unite objects into simple configurations but not yet in more complex ones, combine two complex objects, and visualize an environment as a whole from different positions.